Economic and environmental assessment of bacterial poly(3-hydroxybutyrate) production from the organic fraction of municipal solid waste - Jon Kepa Izaguirre; Leire Barañano; Sonia Castañón; José A. L. Santos; M. Teresa Cesário; M. Manuela R. da Fonseca; Itziar Alkorta; Carlos Garbisu (Bioresources and Bioprocessing, 2021)
Abstract The management of municipal solid waste is a major logistic and environmental problem worldwide. Nonetheless, the organic fraction of municipal solid waste (OFMSW) is a valuable source of nutrients which can be used for a variety of purposes, according to the Circular Economy paradigm. Among the possible applications, the bioproduction of a biodegradable polyester, poly(3-hydroxybutyrate) [P(3HB)], using OFMSW as carbon platform is a promising strategy. Here, an economic and environmental assessment of bacterial P(3HB) production from OFMSW is presented based on previously published results. The SuperPro Designer® software was used to simulate P(3HB) production under our experimental parameters. Two scenarios were proposed depending on the fermentation medium: (1) enzymatic hydrolysate of OFMSW supplemented with glucose and plum waste juice; and (2) basal medium supplemented with glucose and plum waste juice. According to our results, both scenarios are not economically feasible under our experimental parameters. In Scenario 1, the low fermentation yield, the cost of the enzymes, the labour cost and the energy consumption are the factors that most contribute to that result. In Scenario 2, the cost of the extraction solvent and the low fermentation yield are the most limiting factors. The possibility of using process waste as raw material for the generation of other products must be investigated to enhance economic feasibility. From an environmental viewpoint, the photochemical oxidation potential (derived from the use of anisole as extraction solvent) and the generation of acid rain and global warming effect (caused by the burning of fuels for power generation) are the most relevant impacts associated to P(3HB) production under our experimental parameters.